An Overview of Vanadium and Cell Signaling in Potential Cancer Treatments - Valeria Alejandra Ferretti; Ignacio Esteban León (Inorganics, 2022)
Vanadium is an ultratrace element present in higher plants, animals, algae, and bacteria. In recent years, vanadium complexes have been studied to be considered as a representative of a new class of nonplatinum metal anticancer drugs. Nevertheless, the study of cell signaling pathways related to vanadium compounds has scarcely been reported on and reviewed thus far; this information is highly critical for identifying novel targets that play a key role in the anticancer activity of these compounds. Here, we perform a review of the activity of vanadium compounds over cell signaling pathways on cancer cells and of the underlying mechanisms, thereby providing insight into the role of these proteins as potential new molecular targets of vanadium complexes.